The Dark Side of Social Media: Recommender Algorithms and Mental Health - Simona Mandile (CESifo GmbH, 2025)
This paper investigates the impact of social media algorithms on mental health outcomes. I exploit a quasi-experimental setting combining data from the Dutch Longitudinal Internet Studies for the Social Sciences (LISS) coupled with the introduction of the algorithmic feed on Instagram in 2016. I estimate a differences-in-differences model comparing individuals having an Instagram account with individuals who have an account on social media platforms other than Instagram. Using a longitudinal dataset, allows for comparison of the same individuals before and after the introduction of the algorithm. The results show that the introduction of the algorithm on Instagram had a negative impact on teenagers mental health. Furthermore, I show that this effect cannot be attributed to a decrease in stigma surrounding mental health issues or an increased likelihood of individuals reporting such conditions. Additionally, evidence on mechanisms suggests that the results are due to the algorithm on Instagram favoring negative social comparisons.
Keywords: I12; I31; L82; L86; 330; social media; recommendation algorithm; mental health